Olfactory dysfunction is associated with mild cognitive impairment in community-dwelling older adults - Yap, Ai Che; Mahendran, Rathi; Kua, Ee Heok; Zhou, Weibiao; Wang, De Yun (Frontiers in Aging Neuroscience, 2022)
Background: Olfactory impairment is aging-related and associated with cognitive decline in older adults. However, it remains unclear if an olfactory impairment is associated with mild cognitive impairment (MCI) and the degree of impairment in the MCI subtypes. Methods: In a cohort of community-living older adults aged 60 years and above, 670 participants were recruited from the Community Health and Intergenerational (CHI) Study. Olfactory function was assessed using a locally developed nine-item smell test in association with neurocognitive assessments. Analysis of covariances (ANCOVA) was used to examine the association of smell identification score and clinical cognitive status while considering demographic, clinical and neuropsychological factors with Bonferroni correction for group comparisons. Results: Age-related smell detection between normal aging (NA) and MCI participants had no significant difference. The overall mean smell identification score in older adults was negatively correlated with age. The mean smell identification score of MCI participants was also not significantly different as compared to NA, but an amnestic MCI multiple domain (aMCI_MD) subgroup had significantly lower (impaired) mean smell identification scores compared to the NA and MCI single domain (amnestic and non-amnestic) group. Conclusion: This study demonstrated that olfactory identification impairment is a comorbidity in older adults with aMCI and is a potential marker associated with an early stage of a neurocognitive disorder. The smell test could act as a screening tool to help in the early detection of smell impairment for heterogeneous syndromes of mild cognitive impairment among community-dwelling older adults. Clinicians and researchers could benefit from utilizing the locally developed smell test to screen their patients or research participants before the initiation of an appropriate health intervention or in a clinical trial.